Effective way to defend the hypervisor attacks in cloud computing - Muhammad Shahid, Dildar; Nayeem, Khan; Johari, Abdullah; Adnan, Shahid Khan (IEEE, 2017)
Nowadays, the organizations are emphasizing on the security and resilient aspect of the cloud computing to protect the privacy and confidentiality of their data information. However, the hypervisor attack remains a hot issue by the cloud user even though enormous research have accomplished to inhibit the vulnerabilities in the virtualized cloud environment.Therefore, we have proposed the Virtual Machines and Hypervisor Intrusion Detection System, VMHIDS as our technique in detecting and preventing the hypervisor attacks in the virtualized cloud environment. The VMHIDS has adopted several features from the other techniques by inspecting the tasks frequently which then prevent suspicious event occur. Through the VMHIDS, the hypervisor attack is mitigated.